PERAN KEPALA SEKOLAH DAN PENGAWAS DALAM PELAKSANAAN SUPERVISI UNTUK MENINGKATKAN KINERJA GURU - Naila Rahma; Jamilus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the role of principals and supervisors in implementing supervision as an effort to improve teacher performance. The problem studied focuses on the suboptimal implementation of supervision, which results in low quality teacher performance. The method used in this study is a literature study using various sources, including books and scientific articles. The data collection process was carried out through searching, grouping, and analyzing various references related to educational supervision, the role of the principal, and the duties of supervisors. The results of the study indicate that principals have a strategic role in implementing academic supervision directly in the school environment, specifically in fostering and improving the quality of teacher learning. In addition, supervisors play a role as coaches who provide direction, assessment, and reinforcement in the implementation of supervision implemented by the principal. Good cooperation between the principal and supervisor is a crucial element in the progress of supervision. The implementation of supervision that is used in a planned, systematic, and sustainable manner has been proven to improve the professional and pedagogical competence of teachers. In addition, the success of supervision also depends on the understanding and supervisory skills of the implementers. Therefore, improving the capabilities of principals and supervisors in implementing optimal supervision is essential. Therefore, it can be formulated that supervision carried out optimally with the assistance of the principal and supervisor can optimize teacher performance in real terms.